The teaching assistant's guide : an essential textbook for foundation degree students - Hammersley-Fletcher, Linda; Lowe, Michelle; Pugh, Jim. (New York : Routledge, 2006)
This textbook, designed specifically to meet the needs of Foundation Degree students, provides an accessible overview of the teaching assistant's role, incorporating practical tasks that should challenge students and improve their day-to-day practice
Includes bibliographical references and index.
Keywords: Teachers' assistants; Teachers' assistants -- Handbooks, manuals, etc